Peningkatan Pengetahuan Remaja Putri Melalui Edukasi Gizi Menggunakan Media Whatsapp Group - Wardhani, Dwi Aulia; Nissa, Choirun; Setyaningrum, Yahmi Ira (Universitas Muhammadiyah Semarang, 2021)
Chronic Energy Deficiency (KEK) in adolescent girls is one nutritional problem with a high prevalence in Indonesia at 2018 namely 14.5%. One of the causes is wrong eating behavior, based on knowledge and attitude nutrition who lack. The alternative to increase knowledge and attitudes isthrough nutrition education. This research was conducted to analyze the effect of nutrition education on KEK using media whatsapp group to increasing knowledge and attitudes of adolescent girls at SMPN 21 PPU. The research design uses quasi-experimental with group pretest-posttest design. The sample in this study was determined based on convenience sampling technique so that 40 respondents were obtained. Wilcoxon test results indicate that there is an influence of nutrition education on increasing knowledge of adolescent girls (p = 0,000). Wilcoxon test results indicate that there is no effect of nutrition education on improving attitudes of adolescent girls (p = 0.936). The conclusion of this study is that there is an effect of nutrition education on KEK using media whatsapp group toincreasing the knowledge of adolescent girls at SMPN 21 PPU Kaltim, but there is no effect of nutrition education on KEK using media whatsapp group to improving attitudes of adolescent girls at SMPN 21 PPU Kaltim. Based on this, further research is needed to improve attitudes and behavior of foodconsumption in order to avoid KEK.Keywords: KEK, Whatsapp Group, Knowledge, Attitude, Adolescent Girls